1992
DOI: 10.1103/physreva.45.5632
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of disklike hard-core mesogens

Abstract: We report a computer-simulation study of a system of "hard cut spheres, " oblate particles that are obtained by slicing off' the top and bottom caps of a sphere at a distance L/2 from the equatorial plane. This system serves as a model for a disklike mesogen. The phase behavior of this system is found to be strongly dependent on the length-to-width ratio (L /D) of the particles. In addition to isotropic and solid phases, we find nematic and columnar phases for L /D =0.1. For L/D =0.2 we find a columnar phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
373
5
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 399 publications
(416 citation statements)
references
References 17 publications
(58 reference statements)
37
373
5
1
Order By: Relevance
“…Model systems of colloidal platelets that do show the I-N transition have recently become available [34,35], confirming both Onsager's theory and computer simulations [36]. From computer simulations by Veerman and Frenkel [37], and later Zhang et al [38], it was found that hard platelets may also form another liquid-crystal phase, namely the orientationally and 2D translationally ordered columnar (C) phase. This phase has also been observed experimentally in suspensions of sterically stabilised and charged colloidal plates [39][40][41].…”
Section: Introductionmentioning
confidence: 64%
“…Model systems of colloidal platelets that do show the I-N transition have recently become available [34,35], confirming both Onsager's theory and computer simulations [36]. From computer simulations by Veerman and Frenkel [37], and later Zhang et al [38], it was found that hard platelets may also form another liquid-crystal phase, namely the orientationally and 2D translationally ordered columnar (C) phase. This phase has also been observed experimentally in suspensions of sterically stabilised and charged colloidal plates [39][40][41].…”
Section: Introductionmentioning
confidence: 64%
“…13 In fact, the Onsager theory also overvalues the coexisting number densities as compared to the simulations. It turns out that Parsons' approach both narrows the miscibility gap and shifts the coexisting densities …”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of three-body interactions in terms of the ratio B 3 /B 2 2 (with B 3 the third virial coefficient) has been estimated by Onsager 1 at O(1). More accurate predictions were obtained from computer simulations, 13 giving B 3 /B 2 2 ≈ 0.51 for disks with aspect ratio L/D ) 0.1. These results clearly indicate that Onsager's approach of truncating the free energy after the second virial coefficient cannot be justified (quantitatively) for systems of platelets.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…liquid crystals). For details, the reader is referred to refs [36,37,38,39,40,41]. Finally, thermodynamic integration techniques are particularly useful to compute the Gibbs free energy of mixtures.…”
Section: Reference Systemsmentioning
confidence: 99%